INTEGRATING AI CHATBOT INTO LEARNING MANAGEMENT SYSTEM: ENHANCING STUDENT ENGAGEMENT AND LEARNING OUTCOMES - Saifullah, Saifullah; Yawan, Hendri; Syafitri, Nining; Nurhaliza, Sitti (Dharmas Education Journal (DE_Journal), 2024)
This study investigates the integration of chatbots into Learning Management Systems (LMS) to enhance educational experiences, addressing the challenge of student engagement and support in digital learning environments. Utilizing a Research and Development (R&D) approach, the study systematically developed and implemented a chatbot within the "Mesikola" LMS, analyzing data from surveys, interviews, and pilot testing to assess functionality, usability, and learning outcomes. The data revealed high user satisfaction with features such as real-time feedback and multilingual support, with 87% of students reporting improved engagement and 75% experiencing increased self-efficacy. Additionally, 68% of participants demonstrated enhanced academic performance, showing a 15% increase in quiz scores. These findings suggest that well-designed chatbots can significantly contribute to personalized learning and student motivation, providing essential support in educational contexts. The implications of this study underscore the potential for chatbots to transform learning experiences by fostering greater student autonomy and engagement, although further research is needed to refine their effectiveness in collaborative learning environments.